Pelatihan Regulasi Emosi dan Manajemen Konflik untuk Membentuk Pertemanan Sehat Pada Remaja - Qurrota Ayuni Fitriana; Fitrania Maghfiroh; Lely Nur Azizah; Meita Santi Budiani; Satiningsih; Hanif Firdaus G.I.N (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2026)
Adolescence is a transitional phase characterized by high emotional fluctuations due to social dynamics and academic pressures. Problems such as student difficulty managing emotions and poor communication skills, which can lead to conflict, were identified at a partner school, Khadijah High School in Surabaya. This Community Service program aims to equip students with the skills to regulate emotions and resolve peer conflicts to foster healthy friendships. The training program involved 30 students. The training covered two main aspects: healthy emotional regulation and solution-oriented conflict management techniques. Evaluation of the training program was conducted by comparing participants' understanding before and after the program using pre- and post-tests. The results showed an increase in students' understanding of emotional management and adaptive conflict management strategies for applying in friendships. Students are expected to better recognize emotional triggers and choose wise responses when facing differences of opinion with friends. This positive impact is expected to strengthen students' social skills in facing academic and interpersonal challenges, supporting a more harmonious school climate.Keywords: Emotional Regulation, Conflict Management, Friendship, Adolescence